The effect of personality characteristics combined with behavioral activation system (BAS) / behavioral inhibition system (BIS) and sport emotional induction on working memory - Entezari Marzieh; Dehkordi Parvaneh Shamsipour; Heidari Mahtab (Sciendo, 2022)
Study aim: To investigate the interactive effects of behavioral activation or behavioral inhibition and induced pleasant or unpleasant emotions on working memory performance among young adults.